Signaling cascades and the importance of moonlight in coral broadcast mass spawning - Kaniewska, Paulina; Alon, Shahar; Karako-Lampert, Sarit; Hoegh-Guldberg, Ove; Levy, Oren (eLife, 2015)
Many reef-building corals participate in a mass-spawning event that occurs yearly on the Great Barrier Reef. This coral reproductive event is one of earth's most prominent examples of synchronised behavior, and coral reproductive success is vital to the persistence of coral reef ecosystems. Although several environmental cues have been implicated in the timing of mass spawning, the specific sensory cues that function together with endogenous clock mechanisms to ensure accurate timing of gamete release are largely unknown. Here, we show that moonlight is an important external stimulus for mass spawning synchrony and describe the potential mechanisms underlying the ability of corals to detect environmental triggers for the signaling cascades that ultimately result in gamete release. Our study increases the understanding of reproductive chronobiology in corals and strongly supports the hypothesis that coral gamete release is achieved by a complex array of potential neurohormones and light-sensing molecules.
Keywords: coral; cnidarians; mass spawning; reproduction; signalling cascade; moon light